ANALISIS KORAN BINTANG BORNEO: KEHIDUPAN SOSIAL EKONOMI MASYARAKAT BANJARMASIN 1928-1930 - Fathimah Dayaning Pertiwi; Adriana, Adriana; Sainal A (Amarthapura: Historical Studies Journal, 2023)
The socio-economic life of the people of Banjarmasin is based on shipping and trade activities. This research aims to find out: (1) Find out about the social life of the people in Banjarmasin. (2) Knowing the economic life of the people in Banjarmasin. This research uses a historical research method which consists of four stages. The first stage is Heuristic which consists of two sources. The primary sources used in this research are the Bintang Borneo Newspaper and books by Nawawi, Ramli et al. Which is entitled History of the City of Banjarmasin. The second stage is Verification. The third stage of Interpretation. Fourth stage Historiography. This research also uses sociological and economic approaches. The results of this research show that the socio-economic life of the people of Banjarmasin focuses on trading activities carried out on river banks and at night markets to meet their living needs.